Analysis of the Influence of Soil Resistance on the Substation Grid Grounding System - Fitriani, Ayu; Anwar Syahputra, Syofyan; Hidayat, Jhoni (Emitor: Jurnal Teknik Elektro, 2024)
The grounding system is one of the security systems in substations to channel excess voltage caused by lightning strikes that occur at substations, as well as electrical equipment. To design a grounding system, several factors must be considered, including the type of soil, the configuration of the grounding system, the resistivity of the soil, and the condition of the surrounding environment. This research aims to determine the safe limit in the substation grounding system which is influenced by the type of soil in the emergence of touch voltage and step voltage which can be dangerous to humans. The method used is simulation with the Finite Element Method (FEM). The overall result is that with variations in area and soil type, the highest resistance values and touch and step stress values are found in rocky soil types. The touch and step voltage values are within safe limits and do not harm humans, namely in swampy soil where the actual touch voltage value is smaller than the permitted touch voltage value. For the actual touch voltage on rocky soil and wet soil, the actual touch voltage value is greater than the actual touch voltage value, this is within the unsafe limit and can be dangerous to humans. The actual step stress value also results in the actual step stress value being smaller than the permitted step stress value, this is included in safe conditions, and for rocky and wet soil types the actual step stress value is greater than the permitted step stress value, this is included in the condition unsafe and can harm humans.